Crustal and thermal structure of the Permian – Jurassic Luangwa – Lukusashi – Luano Rift, Zambia: Implications for strain localization in magma – Poor continental rifts. (March 2021) - Matende, Kitso N.; Atekwana, Estella; Mickus, Kevin; Abdelsalam, Mohamed G.; Atekwana, Eliot A.; Evans, Rob; Nyalugwe, Victor N.; Emishaw, Luelseged
Abstract: This work uses aeromagnetic, satellite gravity, and ground gravity data to image the thermal and crustal structures beneath the NE-trending Paleozoic - Mesozoic Luangwa – Lukusashi – Luano (LLL) rift in southeastern Zambia. This rift extends between the Precambrian Irumide metacraton in the northwest and the Niassa craton to the southeast and is partially controlled by the NE-trending Mwembeshi suture zone between the two blocks. Although the LLL rift is suggested to have been reactivated by the Southwestern Branch (SWB) of the East African Rift System (EARS), this work did not find shallowing of Curie Point Depth (estimated from the spectral analysis of aeromagnetic data) that would be indicative of elevated heat flow beneath the rift. Three-dimensional inversion of the aeromagnetic data shows a number of magnetized bodies, the largest occurring beneath the central part of the LLL rift and extending to a depth of ~35 km. Spectral analysis of the satellite gravity data indicates a ~45 km thick crust beneath the southwestern and central parts and the northeastern tip of the LLL rift. Two-dimensional (2D) forward modeling of the ground gravity data indicates a ~200 km wide and ~12 km thick under-plated mafic body (UPMB). These results support limited reactivation of the LLL rift by the SWB of the EARS. Further, extensional strain localization during the onset of the LLL rifting is attributed to the accretion of the UPMB beneath the crust. Highlights: Crustal and thermal structures of the Luangwa – Lukusashi – Luano rift were examined. It is a Permian – Jurassic rift in southeastern Zambia. No elevated heat flow is found indicating lack of magmatic activities beneath the rift. The lack of elevated heat flow also indicates the lack of significant rift's reactivation. Thicker crust is found beneath the rift resulting from mafic magmatic under-plating.